The first boundary-value problem for a fractional diffusion-wave equation in a non-cylindrical domain. (December 2017) - Pskhu, A. V.
Abstract: We solve the first boundary-value problem in a non-cylindrical domain for a diffusion-wave equation with the Dzhrbashyan– Nersesyan operator of fractional differentiation with respect to the time variable. We prove an existence and uniqueness theorem for this problem, and construct a representation of the solution. We show that a sufficient condition for unique solubility is the condition of Hölder smoothness for the lateral boundary of the domain. The corresponding results for equations with Riemann– Liouville and Caputo derivatives are particular cases of results obtained here.